INTRODUCTION TO NUTRITION AND EXCERSICE ON PKK CADRES DURING THE COVID-19 PANDEMIC TIME IN GAJI VILLAGE, DEMAK - Sumarawati, Titiek; Chodidjah, Chodidjah; Widayanti, Eni; Fatmawati, Dina (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2022)
Corona Virus Disease 2019 or commonly abbreviated as COVID-19 is an infectious disease caused by SARS-CoV-2. People with COVID-19 may experience fever, dry cough, and difficulty breathing. With the outbreak, the government gives appealed to the community to leave the house as necessary, work from home and maintain health. Salary village is a village located in Demak Regency, Central Java. Public knowledge about the COVID 19 pandemic is still limited, most people do not know that nutrition and physical exercise can improve the body's immune system and prevent COVID 19 disease. Community service is carried out in Gaji Village due to low public knowledge about nutrition and physical exercise (exercise) during the Covid 19 pandemic. Activities were carried out by providing pre and post-tests, counseling to increase public knowledge, and measuring Body Mass Index with 23 participants. Knowledge about Covid 19 increased but not very significantly while increasing knowledge about nutrition and physical exercise experienced a significant increase among the pre and post-test participants. The results of the BMI measurement of 23 respondents had an ideal body weight of 9 people (39.13 %), overweight 12 people (52.17%), and 2 people obese (8.70%). BMI ideal body weight 39.13%; overweight 52.17% and 8.70% fat.